Enantioselective Ring Opening Reactions of Azabenzonorbornadienes with Carboxylic Acids. Issue 20 (16th September 2016) - Zhou, Yongyun; Gu, Cuiping; Chen, Jingchao; Zhu, Meina; Yang, Fan; Xu, Jianbin; Fan, Baomin
Abstract: The palladium/silver (Pd/Ag) co‐catalytic system was found to be effective for the enantioselective ring opening reactions of the low reactive azabenzonorbornadienes with weak nucleophilic carboxylic acids. Both aryl and alkyl carboxylic acids are suitable nucleophiles and afforded the cis ring opening products in good yields with excellent enantioselectivities. The absolute configuration of one of the products has been confirmed by X‐ray crystal structure analysis, and a plausible reaction pathway is proposed. Abstract :